A Xesta de cómo América nasceu da melodía, a special Argonautica - Amado Rodríguez, Mª Teresa (Madrygal. Revista de Estudios Gallegos, 2011)
During his long and fruitful stay in Cuba, Jesuit José Rubinos, born in Corunna, published most of his literary production: hundreds of editorials and research articles, the epic poem entitled 'Covadonga', the short drama piece 'O Velliño', several poem collections of his own lyrical creations and some odd poems which saw the light in magazines and newspapers or were published as loose leaflets. This is the case of 'A Xesta de cómo América nasceu da melodía', a work of classical inspiration which will be studied in this paper, by focusing on the analysis of its characteristics and its debt to classical tradition.
Keywords: Rubinos; poetry; classical tradition.